Impact of Pre-Pregnancy BMI On Short-Term Maternal and Perinatal Outcomes: A Cross-Sectional Study at Lahore - Maham Sultan; Kurrat ul Aaien; Shazia Tufail; Nilofar Mustafa; Javaria Ahmad; Humaira Tabassum (Life and Science)
Objective: To compare short-term maternal and perinatal outcomes in women with normal BMI (<25 kg/m2) and high BMI (>25 kg/m2). Study Design: Analytical cross-sectional study. Place and Duration of Study: This study was conducted in the Department of Obstetrics and Gynecology at CMH Lahore from April 2023 to February 2024. Methods: The women’s BMI at the first antenatal visit was noted by patient records, and they were categorized first antenatal visit noted from patient records, and they were categorized as having a normal BMI (<25 kg/m2) and high BMI (>25 kg/m2). Maternal outcomes considered were pre-eclampsia, gestational hypertension, gestational diabetes, fever, prolonged surgery time, and postpartum hemorrhage. Perinatal outcomes considered were the mode of delivery, gestational age at delivery, duration of labor, APGAR score at 1 minute and 5 minutes, birth weight, birth condition, admission in neonatal ICU, neonatal mortality, and hypoglycemia.  For data analysis, SPSS version 26.0 was used. The chi-square test was applied to evaluate the significance of the association between the variables. Results: Out of 151 women, 102 (67.5%) had normal BMI and 49 (32.5%) had a high BMI on their first antenatal visit. Increased frequency of gestational hypertension (P = 0.021), pre-eclampsia (P = 0.0003), prolonged surgery time (P = 0.022), and macrosomia (P = 0.009) were found to be associated with high pre-pregnancy BMI. Conclusion: The study emphasizes a strong association between maternal pre-pregnancy BMI with gestational hypertension, pre-eclampsia, birth weight, and surgery time. It also calls attention to the need for increased prenatal and perinatal care so that appropriate protocol can be established for women with high pre-pregnancy BMI.